Use of Serum Copper and Chromium as Biochemical Markers in the Diagnoses of Cancer in female subjects - Mohammad Yousaf, Ambreen, Sunbal Khaliq, Adil Yousaf (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To find and compare Copper and Chromium serum levels in female cancer patients of different age groups in Peshawar city. Study design: Comparative analytical study. Place and duration: The study was conducted from 13/ 9/21 to 12/3/22 in Institute of Radiotherapy and Nuclear Medicine (IRNUM) Peshawar. Methods: Patients include 116 female cancer patients divided into three classes age wise designated as A1, A2 andA3. Serum Cu and Cr were quantitatively analyzed by Atomic Absorption Spectrophotometer using acetylene flame (Model Perkin Elmer AAS 700). The collected data was analyzed using SPSS software version 22 Results: A1 includes patients below 18 years 28(24.13%), A2 consists of patients in the age range of 18 45 years 32(27.58%) and A3 includes patient above 45 years 56(48.28%). The mean age of A1, A2 and A3 was 11.69, 35.44 and 61.26 years respectively. The mean BMI of A1, A2 and A3 were 19.5, 27.21 and 31.02 respectively. Mean level of Cu in A1, A2 and A3 was 0.20, 0.44 and 0.19mg/L respectively. Mean level of Cr level was 2.78, 1.13 and 2.97 mg/L in A1, A2 and A3 respectively. A very significant correlation was observed between serum Cr and Cu and in A1 (p = 0.02) and A3 (p = 0.04) respectively. Conclusion: We found that mean level of Cu was less than the normal level. Mean of Cr level was found to be greater than the normal serum level of Cr in all the groups. Key words: Copper, Chromium, serum, cancer, Malignant